Adoption of online travel agency platforms by small and medium hotels in Srinagar: Barriers, benefits, and digital readiness - Suhail Majid Shah; Ajaz Dar (Borneo Novelty Publishing, 2026)
Purpose - This study aims to examine the adoption of Online Travel Agency (OTA) platforms, marketing strategies, and operational challenges faced by small and medium-sized hotels in Srinagar. The research focuses on identifying barriers and benefits associated with digital adoption and understanding how these hotels maintain competitiveness in a dynamic tourism environment. Methodology/Design - A qualitative research design was employed, utilizing semi-structured interviews with hotel operators. Thematic analysis was conducted to identify recurring patterns and key themes, providing an in-depth understanding of operational practices and strategic choices.Findings - The analysis revealed five major themes: economic constraints, digital adoption challenges, relational marketing strategies, competitive pressures, and leveraging local cultural identity. While financial limitations restrict formal marketing, personalized guest engagement and promotion of cultural authenticity emerge as critical strategies. Digital tools such as OTAs and social media offer significant opportunities for market visibility but require training and capacity-building for effective use.Originality/Value - The findings highlight the importance of context-specific strategies for small and medium-sized hotels. Recommendations include skill development programs, collaborative marketing initiatives, promotion of local culture, and policy support to enhance competitiveness and sustainability. These insights provide practical guidance for hotel operators, tourism planners, and policymakers in emerging urban tourism destinations.